Participation and model-building: lessons learned from the Bukittinggi workshop - Vanclay, J.K.; Haggith, M.; Colfer, C.J.P. (2003)
FLORES (the Forest Land Oriented Resource Envisioning System) was initially constructred by 50 people during a multidisciplinary workshop in Bukittinggi, Sumatra, in 1999. It proved that a model of a complex system could be constructed in a participatory way by a diverse team; that it could be done with a graphically-based package such as simile; and that the resulting model could remain reasonably accessible to all participants, and could run on an ordinary notebook computer. Many useful insights can be gained through building such a model, and subsequent experience has demonstrated that modelling in this way can foster continuing interdisciplinary collaboration. Participants founded the FLORE Society, a loose collective open to all researchers interested in pursuing the development and use of such models. The Society conducts an e-mail discussion group on FLORES@cgnet.com (subscription request to JVanclay@scu.edu.au)